Caregiver Stress and Elder Abuse - Suzanna Smith (EDIS)
“One out of four people is a caregiver for a family member or friend (AoA). Most of these informal caregivers, as well as paid caregivers who work for agencies or on their own, are able to meet the many challenges of providing care and do an excellent job (National Center on Elder Abuse, 2002). Even so, every year, thousands of reports of elder abuse are confirmed, and unfortunately, elder abuse seems to be on the rise (National Center on Elder Abuse).” This 2-page Family Album Radio transcript was written by Suzanna Smith and published by the UF Department of Family, Youth and Community Sciences, March 2012.